THE USE OF ENGLISH OF THE TEACHERS AND STUDENTS AT STATE JUNIOR HIGH SCHOOL 1 MAGELANG (A PILOT INTERNATIONAL STANDARD SCHOOL) - Widayanti, Sukasih Ratna; Sugeng, Bambang (LingTera, 2014)
This study is aimed at describing the use of English of the teachers and students at State Junior High School 1 Magelang as a pilot international standard school. The objectives of this study are (1) to find out the frequencies and percentages of the use of English spoken by teachers and students and (2) to describe the types of the occurrence of English sentences, clauses, and phrases spoken by teachers and students. This study was descriptive-qualitative. The subjects were two teachers and forty-eight students of 8B and 8C in State Junior High School 1 Magelang in the school year 2010/2011. The object of this study was the transcript of teachers and students’ utterances indicating the use of English during teaching and learning process in the classroom. The data were collected through observation and audio-taped of the teaching and learning processes. The results of the study are as follows. First, the teachers’ frequencies and percentages of English sentences are 176 sentences from the total number of 220 sentences or 80%, while the students’ frequencies and percentages of English sentences are 72 sentences from the total of 92 sentences or 78.26 %. Both the teachers’ and the students’ quality of English is very good since they make only a few incorrect English sentences. Second, the four types of English sentences are declarative, imperative, interrogative, and exclamatory; the two types of clauses found in English sentences are independent clauses and dependent clauses; and the four types of phrases found in English sentences are noun phrases, verb phrases, adjective phrases, and prepositional phrases. Keywords: the use of English, pilot international standard school